Enhanced myocardial protection in failing hearts: comparative outcomes of single-dose Del Nido and conventional blood cardioplegia in emergency low-ejection fraction coronary artery bypass grafting (CABG) - Emced Khalil (Medicinski glasnik, 2026)
Background: Optimal myocardial protection remains challenging in emergency coronary revascularization, especially in patients with severely reduced left ventricular function. Contemporary cardioplegia strategies aim to limit ischemia-reperfusion injury and enhance postoperative ventricular recovery. The aim of this study was to compare operative parameters, early postoperative outcomes, and myocardial functional recovery between single-dose Del Nido cardioplegia and conventional blood cardioplegia in adults with left ventricular ejection fraction (LVEF) ?40% undergoing emergency isolated coronary artery bypass grafting (CABG). Methods: This retrospective study included 150 consecutive patients with left ventricular ejection fraction (LVEF) ?40% who underwent emergency isolated CABG between 2022 and 2024. Patients were assigned to either the Del Nido group (n=80) or the conventional blood cardioplegia group (n=70). Demographics, operative variables, postoperative complications, ventricular function changes, and short-term mortality were analyzed. Myocardial recovery was assessed using ΔEF (postoperative minus preoperative LVEF). . Results: The Del Nido group demonstrated significantly shorter aortic cross-clamp and cardiopulmonary bypass times and required less intraoperative defibrillation. The incidence of postoperative atrial fibrillation was lower in the Del Nido group (18%) compared with conventional blood cardioplegia (29%). Improvement in ventricular function was greater with Del Nido (ΔEF +5.8±2.1%) than with blood cardioplegia (+3.2±2.4%). Rates of stroke, perioperative myocardial infarction, and early mortality were comparable between groups. Conclusion: Single-dose Del Nido cardioplegia provides effective and safe myocardial protection in emergency low-EF CABG, offering improved operative efficiency and superior early ventricular recovery without increasing perioperative complications.
Keywords: Cardiopulmonary bypass; Coronary artery bypass; Cardioplegic solutions; heart ventricles; myocardial reperfusion injury